THE SOCIO ECONOMIC STUDY OF STREET VENDORS IN M.YAMIN ON THE STREET PASAR RAYA PADANG - Aprila, Dinda - (STKIP PGRI Sumbar, 2014)
The purpose of this study is to get data, obtain, procces, analyze, and discuss about the socio economic study of street vendors in M.Yamin on the street Pasar Raya padang seen from : 1) health conditions, 2) social interaction, 3) income level. This study belong to the descriptive research.Population in this research amounted to 137 peoples the entire all of the street vendors in M.Yamin on the street Pasar Raya Padang and sampling of this study was taken with proposional randonm sampling technique. Samples of this study are 71 peoples. Instruments used in this a questionnaire guided, analysis of data used decriptive statistic by using percentase formula.Resulth of study found: 1) health conditions of the street vendors in M.Yamin on the road Pasar Raya Padang generally suffer from flu and fever during the past year, 2) social interaction vendors in M.Yamin on the road Pasar Raya Padang with the family (father, mother and children) were in love interaction vendors with buyers generally respect each other 3) income levels of the street vendors overage of 630.000 in one week.